GETTING STUDENTS ACTIVELY INVOLVED USING THE â€˜MISTAKE BUSTER TECHNIQUEâ€ TO IMPROVE THEIR NARRATIVE ESSAY - Diana Luspa (Esteem Journal of English Education Study Programme, 2021)
Checking higher Intermediate 2 level studentsâ€™ narrative essay, an idea to get the students actively involved in improving their narrative essay came up. It could not be by just giving the score and gave it back to them. The mistakes can fossilize. So, the â€œMistake Buster Techniqueâ€ was applied. First, the students applied the â€œMistake Buster Techniqueâ€ by doing peer correction to their narrative essay in their first writing. Second, they used the Mistake Buster Techniqueâ€ to find and correct the â€œunidentified mistakesâ€ from their peer correction activity. Their first writing was used as the pretest, while the posttest was taken from their first periodic test. Based on the data analysis, the results of the pretest mean score is 15.48, and the posttest is 17.14.Â  The mean difference is 0.004. The result showed that the â€˜Mistake Buster Techniqueâ€ significantly improves studentsâ€™ narrative essay. It also minimized studentsâ€™ grammatical errors. It was indicated by their grammar pretest mean score 3.36 that improved to 5.00 in their grammar posttest mean score. In additional, this technique allows the students to communicate with their peer in identifying and correcting the mistakes. Another benefit is they can collaboratively identify the possible mistakes themselves. It is a creative activity for the students to take over the role of correcting mistakes. Switching the role of the "mistake corrector" can be used to reinforce theirÂ critical thinking and problem solving. Â Â In short, theâ€ Mistake Buster Techniqueâ€ is very effective and useful to correct their mistakes.